Investigation of the High-Temperature Oxidation Behavior of Ti-Based Alloys Used in the Aerospace Industry - Balci, Esra; Tunç, Büşra; Dagdelen, Fethi (My University, 2025)
In this study, the high-temperature thermal oxidation behavior of the Ti??Nb??Ta?Mo? (at.%) alloy was comprehensively examined through thermogravimetric and differential thermal analysis (TG/DTA). The oxidation experiments were systematically carried out in ambient air to simulate service-like conditions. Uniformly dimensioned alloy specimens were initially subjected to non-isothermal oxidation up to 1000 °C in order to observe the general oxidation trend. Subsequently, isothermal oxidation treatments were conducted at 500, 750, and 1000 °C for a duration of 80 minutes to evaluate the temperature-dependent oxidation kinetics in detail. From the obtained data, the parabolic rate constants were determined as kp??? = 2.54 × 10?? mg·cm?²·s?¹, kp??? = 9.27 × 10?³ mg·cm?²·s?¹, and kp???? = 9.52 × 10?¹ mg·cm?²·s?¹, indicating a significant increase in oxidation rate with temperature. The kinetic analysis revealed that the thermal oxidation process followed a parabolic behavior, suggesting diffusion-controlled oxide scale growth. Furthermore, the apparent activation energy for the thermal oxidation of the alloy was calculated to be 171 kJ/mol, confirming the temperature sensitivity of the oxidation mechanism. In addition, differential thermal analysis (DTA) did not exhibit any prominent endothermic or exothermic peaks, implying the absence of phase transitions or thermal events within the examined temperature range. Overall, the findings contribute to a better understanding of the high-temperature oxidation characteristics of Ti-based refractory alloys and provide valuable insights for their potential use in aerospace and high-temperature structural applications.
Keywords: Activation energy; aerospace industry; Ti base alloys; thermal oxidation behavior